Institutional Oversight and Challenges in Public-Private Partnership: The Cibitung Main Market Revitalization Case - Rahma Wati, Uum; Hakim, Lukmanul; Febriantin, Kariena (Lembaga Junal dan Publikasi, Universitas Muhammadiyah Buton, 2025)
This study aims to evaluate the implementation of the revitalization program of Pasar Induk Cibitung by applying Kadarman’s (2001) control theory, which includes three essential functions: setting standards, measuring performance, and correcting deviations. The research addresses emerging problems in the cooperation between the regional government and private partner, particularly delays in project completion and public service delivery. A qualitative descriptive method was used, involving in-depth interviews, documentation review, and literature analysis. The study reveals that the set standards in physical development, service management, and trader accommodation have not been met. Performance measurements indicate inconsistencies in target achievements and low satisfaction among market users. Moreover, the lack of responsive corrective actions has prolonged unresolved issues, leading to operational stagnation and declining stakeholder trust. The findings underscore the importance of effective supervision mechanisms and institutional commitment to ensure the revitalization goals serve the public interest. This study contributes to improving project oversight practices and informing policy development in the context of public-private partnerships.